The Effect of Work Motivation and Discipline on Employee Performance at Mitra Husada Teluknaga Hospital Tangerang - Muhammad Rizky Khamansyah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Employee performance plays a strategic role in maintaining service quality and organizational sustainability, particularly in the hospital sector where high professionalism and discipline are essential. Work motivation and work discipline are widely recognized as key factors influencing employee behavior and performance outcomes. A quantitative survey approach was applied involving 40 service department employees at Mitra Husada Hospital, Teluknaga, Tangerang. Data were collected through structured questionnaires that had passed validity and reliability testing, followed by analysis using multiple linear regression with SPSS. The findings indicate that both work motivation and work discipline have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination of 65.9% suggests that these variables provide a strong explanation of variations in employee performance, while the remaining percentage is influenced by other factors beyond the research model. These results highlight the importance of strengthening human resource management practices that emphasize motivational enhancement and consistent enforcement of work discipline. From a practical perspective, the implementation of balanced policies combining reward systems, supervision, and clear work regulations is expected to improve employee performance and support sustainable organizational development within healthcare institutions.